In vitro fertilization, endometriosis, nulliparity and ovarian cancer risk - Stewart, L.; Holman, C D.; Aboagye-Sarfo, P.; Finn, Judith; Preen, D.; Hart, R. (Elsevier Inc, 2013)
Objectives. To examine the risk of invasive epithelial ovarian cancer in a cohort of women seeking treatment for infertility. Methods. Using whole-population linked hospital and registry data, we conducted a cohort study of21,646 women commencing hospital investigation and treatment for infertility in Western Australia in the years 1982–2002.We examined the effects of IVF treatment, endometriosis and parity on risk of ovarian cancer and explored potential confounding by tubal ligation, hysterectomy and unilateral oophorectomy/ salpingo-oophorectomy (USO). Results. Parous women undergoing IVF had no observable increase in the rate of ovarian cancer (hazard ratio [HR] 1.01; 95% confidence interval [CI] 0.35–2.90); the HR in women who had IVF and remained nulliparous was 1.76 (95% CI 0.74–4.16). Women diagnosed with endometriosis who remained nulliparous had a three-fold increase in the rate of ovarian cancer (HR 3.11; 95% CI 1.13–8.57); the HR in parous women was 1.52 (95% CI 0.34– 6.75). In separate analyses, women who had a USO without hysterectomy had a four-fold increase in the rate of ovarian cancer (HR 4.23; 95% CI 1.30–13.77). Hysterectomy with or without USO appeared protective. Conclusions. There is no evidence of an increased risk of ovarian cancer following IVF in women who give birth. There is some uncertainty regarding the effect of IVF in women who remain nulliparous. Parous women diagnosed with endometriosis may have a slightly increased risk of ovarian cancer; nulliparous women have a marked increase in risk.